ENTERPRENEUR TERHADAP KINERJA UKM DI KOTA MEDAN - Maya Sari (Jurnal Riset Akuntansi dan Bisnis, 2014)
Development will be more successful if it is supported by enterpreneurs who can create jobs because the government is very limited capabilities. UKM in the city of Medan is an industry that still exist because this field of activities is not affected by the crisis. Increase in units small and medium enterprises can not be separated from the role of enterpreneurial UKM. So in this study, the authors raised the title